A description of projective contractions in the Orlicz-Kantorovich Lattice - Ganiev, Inomjon; Azram, Mohammad (Faculty of Computer and Mathematical Sciences, 2015)
Abstract: In the present paper we show that any positive projective contractions Q with Q1=1 in the Orlicz-KontorovichLattices can be represented in the form for any and for almost all where is conditional expectation operator. Using this result we get abstract characterization conditional expectation operators in the Orlicz-Kontorovich -Lattice